2020
DOI: 10.3390/cells9081896
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Therapeutic Targeting of Cancer Stem Cells within the Tumor Microenvironment: An Updated Review

Abstract: Despite great strides being achieved in improving cancer patients’ outcomes through better therapies and combinatorial treatment, several hurdles still remain due to therapy resistance, cancer recurrence and metastasis. Drug resistance culminating in relapse continues to be associated with fatal disease. The cancer stem cell theory posits that tumors are driven by specialized cancer cells called cancer stem cells (CSCs). CSCs are a subpopulation of cancer cells known to be resistant to therapy and cause metast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 418 publications
0
70
0
Order By: Relevance
“…At present, the origin of CSCs is not yet fully understood. Recent studies have shown that tumor microenvironment (TME), which is composed of immune cells, perivascular cells, fibroblasts and factors secreted by these cells, can provide extracellular signals for the generation and maintenance of CSCs (Dzobo et al, 2020 ). It was recently reported that chemotherapy could cause immunogenic cell death (ICD) of tumor cells, which release damage-associated molecular patterns (DAMPs) into TME (Inoue and Tani, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the origin of CSCs is not yet fully understood. Recent studies have shown that tumor microenvironment (TME), which is composed of immune cells, perivascular cells, fibroblasts and factors secreted by these cells, can provide extracellular signals for the generation and maintenance of CSCs (Dzobo et al, 2020 ). It was recently reported that chemotherapy could cause immunogenic cell death (ICD) of tumor cells, which release damage-associated molecular patterns (DAMPs) into TME (Inoue and Tani, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main contributors to tumor heterogeneity are tumor cell evolution, stromal component contribution, and spatial differences occurring during tumor cell differentiation [11][12][13][14][15][16]. Based on the hierarchical organization of tumor cells, cancer stem cells are tumor-initiating cells capable of self-renewing and differentiating into non-tumorigenic cells [14,17,18]. Thus, cancer stem cells propel tumor formation, its progression, and the formation of secondary tumors [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor resistance reduces the efficacy of current therapies resulting in relapse, progression, and subsequent patients' death [ 25 ]. CSCs referred to as tumor-initiating cells, are increasingly recognized as a key factor in tumor progression, metastasis, and drug resistance [ 13 , 15 ]. In this study, we established an orthotopic mouse model of primary lung cancer and cultured the mice under CIH conditions to mimic the process in the comorbidity of primary lung cancer and OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Lung CSCs have been previously isolated based on the presence of cell surface markers, including CD133 and CD44 [ 13 , 14 ]. Hypoxia is increasingly recognized as owing the potential to exert a significant effect on the maintenance and evolution of CSCs [ 15 , 16 ]. In contrast to continuous hypoxia, CIH in patients with OSA is a unique physiological state with a phase of post-hypoxic re-oxygenation.…”
Section: Introductionmentioning
confidence: 99%